C–C coupling between trinitrothiophenes and triaminobenzenes: zwitterionic intermediates and new all-conjugated structures. Issue 18 (14th April 2016) - Boga, C.; Micheletti, G.; Cino, S.; Fazzini, S.; Forlani, L.; Zanna, N.; Spinelli, D.
Abstract : An aromatic substitution reaction between trinitrothiophenes and sym -triaminobenzenes: new Wheland–Meisenheimer intermediates, bromo- and nitro-substitution, and unexpected formation of 1-nitroso-2, 4, 6-triaminobenzenes. Abstract : The reactions of 1, 3, 5-triaminobenzene derivatives with 2, 3, 4-trinitrothiophene and 2-bromo-3, 4, 5-trinitrothiophene gave new all-conjugated compounds bearing both an electron-withdrawing and an electron-donor moiety on the same unit. The reactions with 2, 3, 4-trinitrothiophene offered evidence, by NMR spectroscopy at low temperature, of the formation of new labile Wheland–Meisenheimer intermediates whereas at room temperature stable unexpected products derived from the attack of the nucleophile at C-4 with replacement of the nitro group were isolated. Their formation caused, in turn, the obtainment of a salt between 1-nitroso-2, 4, 6-triaminobenzenes and 2, 4-dinitrothiophen-3-ol. The reactions with 2-bromo-3, 4, 5-trinitrothiophene produced in good yields the SN Ar substitution product with the displacement of the bromide. All the new coupling products obtained are of applicative interest, considering the increasing concern for highly conjugated π-systems in solar energy conversion or optoelectronic devices.